Application of Green Technology in Digital Supply Chains to Improve Sustainability Performance - Aswadi Jaya; Ramzi Zainum Ikhsan; Nasrul Hidayat; Alfri Adiwijaya; Te Hemi Zane (Technomedia Journal, 2026)
The rapid development of the digital industry has encouraged companies to transform conventional supply chain systems into digital supply chains that are more transparent, efficient, and data-driven. However, this transformation still faces sustainability challenges, particularly related to energy consumption, carbon emissions, operational waste, and inefficient resource utilization. This study aims to analyze the application of green technology in digital supply chains and examine its influence on sustainability performance through the mediating role of digital supply chain systems. A quantitative approach was employed by collecting data from 120 respondents involved in supply chain activities, including business actors, logistics managers, operational staff, procurement staff, distribution staff, and managerial decision-makers in the Jabodetabek area. The data were gathered using Likert-scale questionnaires and analyzed using the SEM-PLS method to test the relationships among green technology, digital supply chain, and sustainability performance. The findings show that green technology has a positive effect on digital supply chains and sustainability performance. Digital supply chains also positively influence sustainability performance and mediate the relationship between green technology and sustainability performance. The model explains 46.4% of the variance in digital supply chains and 68.1% of the variance in sustainability performance. he integration of green technology with digital supply chains can strengthen operational efficiency, reduce environmental impact, improve transparency, and sup- port sustainable business practices. This study contributes to the development of sustainability-oriented supply chain strategies aligned with SDG 9, SDG 12, and SDG 13.